FENOMENA PENGGUNAAN INSTAGRAM SEBAGAI AJANG EKSISTENSI DIRI (STUDI DESKRIPTIF KUALITATIF PADA KALANGAN REMAJA DI SMA MUHAMMADIYAH 7 SURABAYA) - Alifah, Sheila Nur; Hamim, Hamim; Wibowo, Judhi Hari (representamen, 2018)
This research is a qualitative descriptive research that aims to describe the use ofinstagram as a means of self-existence. The object of this research is among teenagers ofSMA Muhammadiyah 7 Surabaya students. In this study, the theory used is the theory ofDramaturgy which is the work of Erving Goffman and supported also with Self-Actualization Theory of Abraham Maslow.The results showed that all informants used inthis study revealed that they often upload photos in social network instagram just to try topresent themselves as possible, in order to achieve the desired goal This is one form ofexistence in using social media. Several informants also revealed that Instagram is amedium that is considered to improve the existence of its users with various featuresowned so that Instagram users trying to show themselves the best to get the desired selfimage.Keywords: Instagram, self-existence, adolescence, dramaturgy, self-actualization maslow